2019
DOI: 10.3177/jnsv.65.8
|View full text |Cite
|
Sign up to set email alerts
|

Effects of All-<i>Trans</i> Retinoic Acid on Lipopolysaccharide-Induced Synovial Explant

Abstract: The present study was conducted to assess the effect of all-trans retinoic acid (ATRA) on synovial explants from rats with rheumatoid arthritis (RA) induced by lipopolysaccharides (LPS). In our study, synovial membranes were excised from the knees of healthy adult Wistar female rats under sterile conditions. We first investigated the synoviums incubated in a control medium or in a medium containing 10 mg/mL LPS, each for 24, 48, and 72 h (LPS-experiment). The changes in inflammatory response from the synoviums… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 38 publications
1
4
0
Order By: Relevance
“…IL-6 is one of the pro-inflammatory cytokines most associated with the pathogenesis of RA, and is abundant in synovial fluid and serum of patients with RA (26). ELASA results showed that TNF-a can induce synovial membrane to produce a large amount of IL-6, reaching a high point after 24 h of incubation and then gradually decreasing, which was similar to the results of previous studies (20). It is possible that mechanical stimulation in the anatomical process causes IL-6 to surge and tends to stabilize over time.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…IL-6 is one of the pro-inflammatory cytokines most associated with the pathogenesis of RA, and is abundant in synovial fluid and serum of patients with RA (26). ELASA results showed that TNF-a can induce synovial membrane to produce a large amount of IL-6, reaching a high point after 24 h of incubation and then gradually decreasing, which was similar to the results of previous studies (20). It is possible that mechanical stimulation in the anatomical process causes IL-6 to surge and tends to stabilize over time.…”
Section: Discussionsupporting
confidence: 88%
“…The separated hindlimb tissues were soaked in 75% alcohol (Sinopharm Chemical Reagent Co., Ltd.) for 2 min, and then quickly removed and put into a pre-cooled phosphate-buffered saline (PBS) solution supplemented with penicillin and streptomycin (HyClone, Logan, UT, USA), temporarily stored in an ice box. Referring to the synovial membrane separation method adopted in the previous studies (20) and made some improvement, after separating synovial membrane and patellar ligament, quadriceps femoris was separated from the femoral shaft to the tibial end by sticking to the upper end of the femur. Since the synovial membrane covered the tendon surface, the quadriceps femoris could be gently lifted to completely expose the synovial membrane connected with the tendon.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…One of the main reasons might be that the early cytokines such as TNF- α , IL-1 β , and IL-6 peak shortly after LPS injection and return to the baseline levels within hours [16], providing one explanation for the negative results observed in our study. Indeed, a number of studies have shown that proinflammatory cytokines and anti-inflammatory cytokines return to normal after 24 hours after LPS stimulation [16, 31, 32]. Depression is one of the most common symptoms observed in sepsis patients [2, 3].…”
Section: Discussionmentioning
confidence: 99%